(untitled) (Bangladesh Medical Journal, 2019)
Co-existence of systemic lupus erythematosus and ankylosing spondylitis is not common. In this report, we present a 24-year-old woman with both the entities diagnosed in the course of time. Initially she presented with malar rash, photosensitivity, oral ulcer and polyarthritis. Her ANA and anti-Smith antibody were positive, but ant-ds DNA was negative. With these features, she was diagnosed as a case of systemic lupus erythematosus. Few months later, she was diagnosed with ankylosing spondylitis on the basis of inflammatory back pain and bilateral sacroilitis. Bangladesh Med J. 2017 Sep; 46 (3): 100-103